Phase transition of hollow-porous α-Fe2O3 microsphere based anodes for lithium ion batteries during high rate cycling. Issue 42 (10th October 2016) - Hao, Shiji; Zhang, Bowei; Ball, Sarah; Wu, Junsheng; Srinivasan, Madhavi; Huang, Yizhong
Abstract : In the present paper, hollow-porous α-Fe2 O3 microspheres are prepared via cation etching of zinc citrate microspheres and subsequent thermal treatment. Abstract : In the present paper, hollow-porous α-Fe2 O3 microspheres are prepared via cation etching of zinc citrate microspheres and subsequent thermal treatment. The superior performance of the as-obtained α-Fe2 O3 microspheres as an anode material for lithium ion batteries is evaluated. After 1000 cycles, the capacity still remains more than 1100 mA h g −1 at a current rate of 1 A g −1 . Meanwhile, the crystal size induced phase transition of Fe2 O3 microspheres (α → γ → β) is observed during cycling by the measurements of ex situ XRD and TEM, which is responsible for their abnormal performance fluctuation.